(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study presents a philosophical and detailed analysis of the ecological thought of Murray Bookchin, the American philosopher and founder of the theory of social ecology in the twentieth century. The primary aim is to offer a new and broad perspective on the relationship between the environmental crisis and contemporary social and political systems, which have a direct impact on the future of humanity and life on Using a descriptive and analytical approach, the study highlights Bookchin’s life and his scientific and philosophical works, along with the historical development of the concept of social ecology as one of the fundamental concepts of critical thought concerning the essential relationship between human beings and nature. The philosophy of ecology is presented in a precise, systematic, and scientific manner, especially its fundamental and profound criticisms of capitalism and systems of governance. Bookchin does not view the environmental crisis as merely a technical or scientific one that can be solved with technological fixes; rather, he sees it as a reflection of a deeper, broader social and political crisis that requires fundamental social solutions. He believes that the roots of this crisis lie in the structure of economic and political systems, thus necessitating radical changes for the reorganization of society. The most important conclusion is that Bookchin’s ideas on libertarian municipalism, social self-management, and direct democracy offer a powerful and practical alternative for successfully confronting the environmental crisis and building a just society that is in balance with the environment.